PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS V SEKOLAH DASAR - Ranianisa Rahmi; Yeni Erita (STKIP Subang, 2022)
This study aims to analyze the role of the Problem Based Learning(PBL) model in integrated thematic learning in elementary schools. The model that has been widely adopted to support the learning centered learning model and emphasizes the involvement of students in the active learning process as in the integrated thematic learning process is the Problem Based Learning(PBL) model. This research is Literature Study. First the researchers formulated the research problem, then proceeded to search for electronic journals via google schoolar. From the search, 15 relevant journals were analyzed for their role in integrated thematic learning using the Problem Based Learning(PBL) model. The keywords used for journal research are Problem Based Learning, learning outcomes, elementary school. The analysis turned out to show that the Problem Based Learningmodel was able to improve student learning outcomes starting from the lowest 28% to the highest 93% with an average of 58%.